(untitled) (Bangladesh Journal of Psychiatry, 2018)
Children and adolescents of this era are experiencing more traumatic events than earlier, resulting in more diagnosed cases of post traumatic stress disorder. One such case is discussed here following exposure to molestation. After assessment and case formulation, an extensive psychological management (Trauma Focused Cognitive Behavior Therapy) was done which is presented through the report. Mentionable improvement was acknowledged by client who paves the way for future evidence-based work. Bang J Psychiatry June 2016; 30(1): 20-22